2016
DOI: 10.1371/journal.pone.0161593
|View full text |Cite
|
Sign up to set email alerts
|

The Qualification of Outcome after Cervical Spine Surgery by Patients Compared to the Neck Disability Index

Abstract: ObjectiveThe Neck Disability Index (NDI) is a patient self-assessed outcome measurement tool to assess disability, and that is frequently used to evaluate the effects of the treatment of neck-related problems. In individualized medicine it is mandatory that patients can interpret data in order to choose a treatment. A change of NDI or an absolute NDI is generally meaningless to a patient. Therefore, a correlation between the qualification of the clinical situation rated by the patient and the NDI score was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…[8,9] In this study disability of patients due to neck pain was assessed using NDI before and after treatment and a significant reduction in scores was observed posttreatment which represented reduction in disability. This goes in agreement with the findings of study done by Donk et al [10] Our study also showed that there is a correlation between NDI and qualitative Likert scale rating which confirmed that improvement in pain status is also associated with reduced disability of patients with neck pain. Donk et al compared the qualification of outcome by patients after cervical spine surgery to the NDI and found that there was a correlation between qualification of the situation by the patients themselves and NDI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[8,9] In this study disability of patients due to neck pain was assessed using NDI before and after treatment and a significant reduction in scores was observed posttreatment which represented reduction in disability. This goes in agreement with the findings of study done by Donk et al [10] Our study also showed that there is a correlation between NDI and qualitative Likert scale rating which confirmed that improvement in pain status is also associated with reduced disability of patients with neck pain. Donk et al compared the qualification of outcome by patients after cervical spine surgery to the NDI and found that there was a correlation between qualification of the situation by the patients themselves and NDI.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also proved qualitative Likert scale as an effective tool to measure the improvement in clinical condition after treatment. [10,11] VAS showed significant reduction in scores following treatment with skeletal muscle relaxants and analgesics in the study population. In their study, Lee et al measured the change in VAS score associated with adequate pain control and a mean reduction in VAS of 30.0 mm was observed which represented a clinically important difference in pain severity with respect to patients' perception of adequate pain control.…”
Section: Discussionmentioning
confidence: 80%
“…It will not help him/her in decision-making about any treatment for neckrelated problems." 32 Therefore, in this study, we have attempted to transform the outcome scores into expressions that can easily be understood by patients to help them in making a decision about their eventual treatment. Here we report that the vast majority of patients in both single and two level cohorts improved in neck disability after surgery (70.2%-80.8% of two-level surgeries and 84.6%-84.8% of single level surgeries) and neck pain (83.3%-87.5% of single level surgeries and 77.7%-86.0% of two-level surgeries).…”
Section: Discussionmentioning
confidence: 99%
“…For data analysis the Student's t test was used. At dichotomisation of outcome, two groups of patients could be defined: those with a good to excellent outcome, and those with a less than good outcome [9]. To estimate the value of DNDI that corresponded best with the dichotomised outcome, the cut-off values with the highest sensitivity and specificity were chosen separately.…”
Section: Methodsmentioning
confidence: 99%